Pharmacokinetics of mycophenolate mofetil in children with lupus and clinical findings in favour of therapeutic drug monitoring. (October 2014) - Woillard, Jean‐Baptiste; Bader‐Meunier, Brigitte; Salomon, Rémi; Ranchin, Bruno; Decramer, Stéphane; Fischbach, Michel; Berard, Etienne; Guigonis, Vincent; Harambat, Jérôme; Dunand, Olivier; Tenenbaum, Julie; Marquet, Pierre; et al.
<x xml:space="preserve">Abstract</x> Aims The use of mycophenolate mofetil (MMF) in children with systemic lupus erythematosus (SLE) is increasing. However, the clinical benefit of its monitoring has been scarcely studied, and little is known about its pharmacokinetics in this context. The objectives of the present study were: (i) to describe mycophenolic acid (MPA, the active moiety of MMF) pharmacokinetics, (ii) to develop a Bayesian estimator (BE) allowing the determination AUC (area under the curve) from a limited number of blood samples and (iii) to explore the relationships between exposure indices to MPA and the clinical status in children with SLE. Methods This was a retrospective study including 36 children with SLE, extracted from the expert system ISBA, for whom full‐ pharmacokinetic profiles of MPA were collected together with clinical data. A pharmacokinetic model and a BE were developed using an iterative two stage Bayesian approach. ROC curve analyses and logistic regressions were used to investigate the association of exposure and active disease. Results A pharmacokinetic model and a BE were developed that allowed good AUC estimation performance (bias ± SD = −0.02 ± 0.15). ROC curve analyses showed that AUC/dose <0.06 and AUC <4 mg l−1 h were associated with a good sensitivity and specificity for active disease (78%/94% and 94%/56%, respectively). When introduced in a logistic regression model, AUC <44 mg l−1 h and AUC/dose <0.06 were associated with an increased risk of active disease (OR = 21.2, 95% CI 2.3, 196.1, P = 0.007 and OR = 59.5, 95% CI 5.9, 588.2, P = 0.0005 respectively]. Conclusions The developed pharmacokinetic BE could be used to test prospectively the interest of MPA monitoring for limiting relapse of the disease or its progression.